Principles of equity and trusts - Hepburn, Samantha J. (The Federation Press, 2009)
This fourth edition of Principles of Equity and Trusts has been comprehensively updated and revised. It retains its original style of presenting principles and remedies relevant to equity and trusts in a straightforward and succinct manner.